Creativity as a Racializing and Ableizing Scientific Object: Disentangling the Democratic Impulse From Justice-Oriented Futures. Issue 1 (March 2022) - Ziols, Ryan; Davis, Natalie Renee; Holbrook, Teri; Bridges, Sarah
In this review of literature, we attend to some of the ways that well-intentioned hopes for fostering creativity and encouraging greater inclusion may also rely on problematic premises that work to reify exclusionary logics and practices. More specifically, we historicize and critically examine how creativity studies—often despite explicit efforts to broaden notions of creativity, include marginalized populations, and democratize education—have differently reanimated racializing and ableizing discourses over seven decades of efforts to scientifically study, define, and/or cultivate creativity. In our emphasis on the relationship between past and present designs, we attend to more pernicious tensions and concerns that continue to hold implications for scholarship, research, policy, and practice.